Value of information and natural resources decision‐making - Byron K. Williams; Fred A. Johnson (Wildlife Society Bulletin)
ABSTRACT Though the potential for information to measurably improve management has been highlighted for several decades, in recent years the “value of information” has surfaced with increasing frequency in natural resources. However, the use of this phrase belies the fact that many in natural resources have only a limited understanding about what it actually means, how to measure it, and what to do with it. We introduce and describe several forms of the value of information in a context of the management of renewable natural resources. The value of information is discussed in terms of a potential gain in value with the addition of new information, as well as a loss in value associated with the absence of information. Value metrics are developed for uncertainty about resource status as well as resource processes and responses to management. We provide a common notation for the metrics of value, and discuss linkages of the value of information to strategic approaches such as adaptive resources management and partially observable decision processes. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.